A Bionic Study of the Magnetic Bacteria with Applications to the Mecano-magnetic Micromanipulators. (2017) - Elena, Yuan FengYuan; Mircea, Ignat; Ioan, Ardelean
Abstract: The paper presents a bionic study of the magnetic bacteria which includes: The structure of the magnetic bacteria ( Magnetospirillum magneticum ) with the of the magnetosomes(which represent the nanomagnetic particles in chains); The motility and the movements; with a biomecanomagnetic model; The identification of the micro and nanomanipulators for MEMS (microelectromechanical) applications. The authors present the microecanomagnetic structures of this manipulators: the geometric model (the linear and the angular movements), the engineering structures with the specific parameters (micro forces, speed, micro torque), and the electromagnetic driver modes of this manipulators.